Report of the Workshop on the Use of Best Available Science in Developing and Promoting Best Practices for Trawl Fishing Operations in Southeast Asia, Bangkok, Thailand, 8-13 September 2014 - (:unkn) unknown (Food and Agriculture Organization of the United Nations, FAO, 2017)
The trawl fisheries of South and Southeast Asia (SSA) are the largest in the world, and their catch is a major component of food security, poverty elimination and employment for the region. To include South and Southeast Asia (SSA) trawl fisheries in the global analysis of trawling impacts, the Trawl Study Committee initiative was conducted on 8–13 September 2014 in Thailand an expert workshop on the use of best available science in developing and promoting best practices for trawl fishing operations in South and Southeast Asia. A total of 22 experts participated in the workshop. As elsewhere, the impact of trawl fisheries on benthic biota in this region will depend on the distribution and intensity of trawling and the sensitivity of habitats. Many benthic biota of shallow water soft bottom tropical habitats are expected to have relatively high recovery rates, and trawling in the favored shallow sandy and muddy areas is expected to have lower impacts than in areas where more sensitive biogenic habitats including sea-grasses and corals are present. The workshop sought to: (1) identify and evaluate data on trawling distributions and impacts in South and Southeast Asia; (2) to develop and propose collaborative arrangements for sharing expertise; and (3) to evaluate best practices for trawling to enhance sustainability of food security, livelihoods and ecosystems. Identifying best practices for the region is difficult because there are complex objectives that include food security and employment, as well as environmental sustainability and other objectives such as protection of artisanal fishing communities from industrial trawl fleets. However, common best practices have emerged, such as limitation on fleet size and composition, provision of no-trawl zones in coastal areas to protect both sensitive habitats and artisanal fishing communities, closed seasons and increasing mesh size do emerge as common themes that are being adopted. An impediment to effective implementation of best practices is the general lack of national governments ability to enforce regulations. There appears to be a general agreement that the amount of trawl effort is more than sufficient to achieve long-term maximum yield, and in many cases there is excessive fishing capacity. It appears that the key to improving regional trawl performance is intense cooperation with the fishing fleets, and relying on the fishing fleets to strengthen self-enforcement of regulations. The workshop served as an excellent first step in building a collaboration with a network of global trawl fishing scientists, and the collaborations identified should lead to a significant advance in our understanding of how to best manage Asian trawl fisheries.